2016
DOI: 10.1021/acs.bioconjchem.6b00174
|View full text |Cite
|
Sign up to set email alerts
|

Development of 99mTc-Labeled Pyridyl Benzofuran Derivatives To Detect Pancreatic Amylin in Islet Amyloid Model Mice

Abstract: While islet amyloid deposition comprising amylin is one of pathological hallmarks of type 2 diabetes mellitus (T2DM), no useful amylin-imaging probe has been reported. In this study, we evaluated two (99m)Tc-labeled pyridyl benzofuran derivatives as novel amylin-imaging probes using the newly established islet amyloid model mouse. Binding experiments in vitro demonstrated that [(99m)Tc]1 displayed a higher affinity for amylin aggregates than [(99m)Tc]2. Autoradiographic studies using human pancreas sections wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Yoshimura et al. reported 99m Tc complexes bearing a pyridyl‐benzofurane (PBF) attached via a triethylene glycol spacer [9] . The best affinity, determined by radiocompetition, was K i =146 n m , two orders of magnitude below the K i of the 125 I‐labelled PBF (2.66 n m ), indicating a strong affinity loss induced by the Tc complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshimura et al. reported 99m Tc complexes bearing a pyridyl‐benzofurane (PBF) attached via a triethylene glycol spacer [9] . The best affinity, determined by radiocompetition, was K i =146 n m , two orders of magnitude below the K i of the 125 I‐labelled PBF (2.66 n m ), indicating a strong affinity loss induced by the Tc complex.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Another example concerns SPECT detection of amylin in the pancreas with a 99m Tc complex. [9] Amyloid deposits in pancreatic islets appear in >90% of type 2 diabetes mellitus (T2DM) patients and their quantity has been recognized as a direct indicator of disease severity. Amylin or islet amyloid polypeptide (IAPP) is a 37-amino-acid peptide co-secreted with insulin by β-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided histological and autoradiographic evidence for in vitro binding of A beta imaging probes to synthetic hIAPP aggregates [26], and when administered intravenously, these agents accumulated in implanted hIAPP aggregates in mice [27]. However, these studies did not determine whether amyloid-imaging probes bind to endogenous islet amyloid, or whether they allow identification of islet amyloid deposits in vivo using PET.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid imaging probes have been designed for PET detection of amyloid beta (A beta) deposits in the brain [2224], and since brain and islet amyloid deposits share structural similarities [25], these probes have been proposed as tools to detect islet amyloid as well. Limited studies have found that some A beta amyloid imaging probes bind synthetic hIAPP in vitro and ex vivo [26,27]. To our knowledge, no studies to date have tested whether these probes can identify and quantify endogenous islet amyloid in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is an unmet need to develop a noninvasive imaging method to quantitatively measure the pancreatic islet amyloid burden in T2DM patients. So far, only one molecular probe, 99m Tc-labeled pyridyl benzofuran, has been evaluated in vivo on the islet amyloid mouse model with single-photon emission computed tomography 10 . It showed a 1.6-fold higher uptake in the pancreas of the model mice than the control mice at 1 h after injection.…”
Section: Introductionmentioning
confidence: 99%